A circularly polarized‐reconfigurable planar end‐fire antenna with bidirectional radiation of same sense and wide beamwidth. Issue 12 (28th October 2020) - Yan, Yang‐Dong; Jiao, Yong‐Chang; Zhang, Chi
Abstract: A reconfigurable, planar, and end‐fire circularly polarized (CP) antenna with wide beamwidth is presented, which exhibits the bidirectional radiation with the same sense by combining two pairs of identical CP elements placed in a back‐to‐back configuration. The design of the element includes a meandering phase delay line, which connects a printed electric dipole and a quarter‐wavelength shorted microstrip patch. Then, eight p‐i‐n diodes are employed in the two dipoles arms to realize either left‐handed CP (LHCP) or right‐handed CP (RHCP) by manipulating the DC bias voltage across p‐i‐n. The prototype is designed to operate at a center frequency of 5.8 GHz with a size of 0.61 × 0.50 × 0.029 ( λ 0 3 ), where λ 0 is the wavelength of the center frequency. Also, its end‐fire beam is in parallel with its plane. Experimental results show that the overlapped bandwidth for 10‐dB return loss and the 3‐dB axial ratio (AR) of the bidirectional end‐fire antenna is from 5.72 to 5.89 GHz for the two CP states. The half‐power beamwidth (HPBW) in the horizontal and vertical plane are 95°/115° at the 5.8 GHz.